(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
At present, banks and financial institutions are using strategic planning to attract and retain customers, as well as to boost their long-term satisfaction; consequently, banks would do well to emulate these practises if they want to succeed. To keep its customers from leaving for a competitor, banks need to design and execute customer-centric initiatives in a consistent manner. Dimensions such as E-banking services, motivating factors, and identifying the challenges associated with E-banking services are necessary for understanding consumer impression of the banking industry. Finding out where customers stand in terms of satisfaction is the focus of the present study. Independent sample t-testing in SPSS 23 was used to look at the responses of 169 people drawn at random from customers of public and commercial banks in Chhindwara. This test is designed to evaluate whether there is statistical evidence that the population means of two separate groups are substantially different by a comparison of their means.